THE UN FRAMEWORK CONVENTION ON CLIMATE CHANGE AND THE PARIS AGREEMENT AS THE BASIS OF GLOBAL CLIMATE POLICY - RIABCHYN, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of the contribution of the UN Framework Convention on Climate Change and the Paris Agreement as the basis for the formation of modern global climate policy. The article states that the concept of climate neutrality is key in the fight against climate change. It is determined that climate change mitigation should be implemented through those technologies and actions that lead to a reduction in GHG emissions, namely the development of renewable energy sources (RES), which reduce the need for fossil fuels, and energy efficiency, the transition to electric vehicles and alternative traditional production methods (e.g., steel), the replacement of fossil fuels with green or low-carbon ones (e.g., hydrogen, biofuels), the use of carbon capture and storage technologies, etc. It was established that the main goal of the Paris Agreement is to keep the global temperature increase within 1.5-2°C by 2100 (according to the IPCC report), since this limit was defined as safe, one that would not lead to catastrophic unforeseen consequences for humanity, increasing the ability to adapt to the adverse effects of climate change, ensuring the consistency of financial flows with the direction of low-carbon and climate-resilient development. It was concluded that the country's recovery will inevitably lead to additional GHG emissions, therefore it is important to choose a recovery concept that minimizes emissions and ensures economic growth without increasing GHG emissions. This is possible within the framework of the concept of "rebuild better than before" with the application of the principles of green recovery during the development of national and regional recovery/reconstruction programs throughout Ukraine.
Keywords: sustainable development; climate neutrality; low-carbon development; global climate policy